Review of wind energy technology and associated market and economic conditions in Spain. (March 2019) - Rosales-Asensio, Enrique; Borge-Diez, David; Blanes-Peiró, Jorge-Juan; Pérez-Hoyos, Ana; Comenar-Santos, Antonio
Abstract: The current EU 2020 reference framework has set a 20% goal for energy coming from non-exhaustive resources. In general, it can be said that the national action plans for renewable energy sources and the biennial control provided in Directive 2009/28/EC, regarding the promotion of the use of energy from renewable sources, have been adequate in encouraging clarity for venture capitalists and other stakeholders and, thus, have favored a rapid development of renewable energy from 10.4% in 2007 to 17% in 2015. Between 2005 and 2013, the Spanish government implemented a renewable aid plan that induced an important boost in the number of wind energy projects facilitated by companies. This scheme was modified in 2013, resulting in a drastic decrease in the investments on wind energy capacity. The reason that this regime was modified not only because of the worldwide economic downturn since 2010 but also owing to the shortcomings of this scheme. The expected venture capitalist behavior with respect to the current energy regime is still uncertain. Given the limited support provided by the Spanish government, any remarkable development seems unlikely. This research suggests that a sudden change in the decreased investments on wind energy capacity is unlikely and the wind energy targets for 2020 will not be achieved if no new policies are implemented. Graphical abstract: fx1 Highlights: In 2013 Spain retroactively modified the remuneration system for wind energy. As a result, the rate of return of wind energy was reduced to seven percent. This governmental arrangement has jeopardized investor certainty. Any remarkable development for the wind energy sector in Spain seems unlikely.